(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Biochar is a carbon material that can be produced from burning biomass. In general, East Nusa Tenggara is rich in untapped biomass. Understanding of the importance of biomass is still in the low category. Therefore, this Community Service activity was carried out to introduce and teach the process of making biochar and its application in Oel’ekam Village, Central Mollo sub-district, South Central Timor district, East Nusa Tenggara. This activity involved 27 participants from 3 farmer groups, namely the Olif Tataf farmer group (Oel’ekam hamlet); the Oemathonis farmer group (Oehala hamlet); and the Tafena Kuan Farmer’s Group (Oel’ekam hamlet) as well as the head of the PKK team in Oel’ekam village and several of its members. The activity began with guidance and training on making biochar using coir and dried coconut shells using the kiln drum modification method (simple pyrolysis), followed by demonstration plots (demonstration plots) using a vermiculture system in the village office environment. The results showed that the participants understood the process of making biochar and its application to viticulture cropping systems as indicated by the observed crop yields after 10 days of activity. Thus, there is a need for continuous assistance for a wider cropping system on farmers’ land.